Nomenclatural and Taxonomic Notes on Eriocaulaceae from the Atlantic Forest, Brazil - Trovó, Marcelo; Echternacht, Livia; Costa, Fabiane; Giuliett, Ana; Sano, Paulo (Phytotaxa, 2015)
The diversity of Eriocaulaceae in the Neotropics is primarily concentrated in the Espinhaço Range in Brazil and in the Tepuis of Venezuela. Species richness outside of these areas, however, is significant but poorly known. Based on improved taxonomic knowledge about Eriocaulaceae in the Atlantic Forest domain in Brazil, we propose nomenclatural and taxonomic changes, and provide an identification key and an annotated list of the species of the core Serra da Mantiqueira. A total of 24 species were found, one described quite recently and two still known only from the type specimens. Lectotypes for the following names are designated: Eriocaulon majusculum, Paepalanthus exiguus, P. jordanensis, P. manicatus, and Syngonanthus caulescens.